Politologia – nauka w drodze - Wolff-Powęska, Anna (Przegląd Politologiczny, 2018)
The paper presents the thesis that the interdisciplinarity of political science as a science, open to the accomplishments in the field of social sciences and humanities enriches this disci- pline. On the one hand, the enormous expansion of knowledge enforces specialization. On the other hand, there is a constant exchange of thought and methodological experience that takes place for fear of becoming isolated. Globalization – the new quality of international life – forces us to continuously exceed the limits of traditional theoretical orientations. Scientific pluralism raises the question of who and when has the right to decide on the superiority of one scientific model over another. The present state of research into the status of political science allows us to observe that the research instruments of politics, the process of permanently changing the world, must be flexible. The history of the social sciences confirms the continu- ous interdependency of particular disciplines and acknowledges political science as an impor- tant link in the chain of evolution of science.